Anomia czasów transformacji – refleksje w perspektywie deprywacji potrzeby bezpieczeństwa osobistego i prawnego - Torczyńska-Jarecka, Monika (My University, 2005)
The article describes the phenomenon of anomy in a society undergoing cultural, political and economic transformations. In a period of rapid change this problem is particularly significant for Polish society, especially in the situation of a crisis of values and deep decomposition of a valid system of social, moral and legal norms. The collective sense (or lack of sense) of legal and personal safety determines social attitudes to a newly established political and legal order. Strong and long-lasting deprivation of the need for safety, characteristic of the present Polish reality, results in many different pathologies in the activities of individuals, and in a long-term perspective of non-individual aberrations, and in consequence in the state of anomy, which overwhelms the whole society.
Anomy in the Times of Transformation - Afterthoughts in the Perspective of Deprivation of Personal and Legal Needs for Safety